(untitled) (Research, Society and Development, 2022)
The use of Botulinum Toxin by dental surgeons (CD) is a complex theme/topic that divided opinions about its legality, it has been the subject of disputes in the judicial sphere. Through the study of the legislation related to the theme and the review of the current literature, this study aimed to demonstrate the legitimacy of the CD, through normative devices and technical arguments to use botulinum toxin in dental practice in a therapeutic, aesthetic and functional way, within anatomical area of performance of this professional. The research that was carried out between the months of February and August 2021, used as a base, law obtained on the Presidency of the Republic website, Resolutions available on the Federal Council of Dentistry (CFO) website, judicial decisions obtained on the Federal Regional Court website and articles found in the database of: Latin American and Caribbean Literature in Health Sciences (LILACS), PubMed and Scientific Electronic Library Online (SciELO). After applying the inclusion and exclusion criteria, 17 publications were selected to reference the research. After careful analysis, it was verified the existence of legal protection, considering Law nº 5,081 / 1966, normatization of the theme, through CFO Resolution nº 176/16 and nº 198/19, and a favorable judicial decision, which legitimize the use of the referred toxin by the CD, in addition to publications that point out its benefits and significant applicability in dentistry, which encourages further studies on the subject, considering that the current literature is still scarce.